Cassava brown streak disease: historical timeline, current knowledge and future prospects - Tomlinson, Katie R.; Bailey, Andy M.; Alicai, Titus; Seal, Sue; Foster, Gary D. (Molecular Plant Pathology, 2018)
Cassava is the second most important staple food crop in terms of per capita calories consumed in Africa and holds potential for climate change adaptation. Unfortunately, productivity in East and Central Africa is severely constrained by two viral diseases: cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). CBSD was first reported in 1936 from northeast Tanzania. For approximately 70 years, CBSD was restricted to coastal East Africa and so had a relatively low impact on food security compared with CMD. However, at the turn of the 21st century, CBSD re-emerged further inland, in areas around Lake Victoria, and it has since spread through many East and Central African countries, causing high yield losses and jeopardizing the food security of subsistence farmers. This recent re-emergence has attracted intense scientific interest, with studies shedding light on CBSD viral epidemiology, sequence diversity, host interactions and potential sources of resistance within the cassava genome. This review reflects on 80 years of CBSD research history (1936– 2016) with a timeline of key events. We provide insights into current CBSD knowledge, management efforts and future prospects for improved understanding needed to underpin effective control and mitigation of impacts on food security.
Keywords: CBSD; CBSV; CMD; Food security; UCBSV; virology